Rapid formation of a dense sulfur layer on gold through use of triphenylmethane sulfenyl chloride as a precursor - Houmam, Abdelaziz (Langmuir : the ACS journal of surfaces and colloids, 2012)
The use of triphenylmethane sulfenyl chloride as a new precursor leads to the efficient deposition of sulfur on polycrystalline gold and Au(111) substrates. The modified surfaces are characterized using X-ray photoelectron spectroscopy (XPS), electrochemistry and scanning tunneling microscopy (STM). The XPS data shows the rapid deposition of polymeric sulfur within very short times. Electrochemical stripping cyclic voltammetry (CV) confirms the rapid deposition and shows that high coverage values are achieved. STM imaging shows the formation of a wide range sulfur layer and production of the well-known etch pits. High-resolution STM images confirm the high density of the sulfur layers and show formation of a long-range phase consisting of rhombus structures close to the previously described rectangular structures along with other parallelograms and partial parallelograms. The present results do not show the initial formation of any organic self-assembled monolayer (SAM) indicating that the formation of polymeric sulfur does not result from the decomposition of an initial SAM as previously observed with alkyl and aryl thiolate-based SAMs. The suggested mechanism involves an initial reductive process similar to the one reported for thiocyanates and sulfenyl chlorides. This is followed by the dissociation of the Ph(3)C-S bond, leaving only sulfur on the surface, through a process leading to the recombination of the remaining fragments to yield triphenylmethyl chloride